The Effects of Different Kinds of Hands-on Modeling Activities on the Academic Achievement, Problem-Solving Skills, and Scientific Creativity of Prospective Science Teachers - ŞAHİN, FATMA (SPRINGER, 2021)
The purpose of the current study is to investigate the effectiveness of unstructured, semi-structured, structured hands-on modeling activities and traditional teaching methods in developing academic achievement, problem-solving skills, and scientific creativity in prospective science teachers in the subject of the human circulatory and respiratory systems. A pre-test-post-test quasi-experimental design was used to investigate the treatment effect. There were three experimental groups and a control group in a total of 88 prospective science teachers who were enrolled in the Department of Science Education. The Academic Achievement Test (AAT), Problem-Solving Inventory (PSI), and Scientific Creativity Scale (SCS) were applied as data collection tools. The researchers employed two-way ANOVA and ANCOVA to analyze the data. Results revealed that all modeling activities were effective in enhancing participants' AAT scores when compared with those of the control group. In addition, unstructured modeling and semi-structured modeling activities were more effective than structured modeling activities in improving AAT scores. For the AAT retention test, unstructured and semi-structured modeling groups showed better performance than the structured modeling group and control group. Moreover, there was a statistically significant difference in PSI scores of the participants in favor of unstructured and semi-structured modeling activities. Lastly, there was no statistically significant difference in SCS scores with the experimental groups and control group.
Keywords: Hands-on modeling; Academic achievement; Problem solving; Scientific creativity; STUDENTS ACHIEVEMENT; SCHOOL; SYSTEM